Diseño e Implementación de un Sistema de Telefonía IP basado en Software Libre para la Empresa Flornintanga S.A - Buestán Arízaga, Álvaro Edwin (2012)
This project has as main objective the design and implementation of an IP telephony network based on a system of free software for Flornintanga Company S.A. for which there was a technology research involving IP telephony, to highlight their concepts, capabilities and advantages. Chapter I provides an overview of the current state of the Company Flornintanga S.A., starting with the mission vision and administrative arrangements, in addition, an analysis of their existing technology infrastructure and service requirements as well as supporting telephony the scope and approach of the project solution...